Study of rheological behaviour of hydroxyethyl cellulose gels in the development of the composition and technology of the medicine with anti-inflammatory activity - Vladyslav Postoy; Halina Kukhtenko; Liliia Vyshnevska; Ievgenii Gladukh; Kateryna Semchenko (Pensoft Publishers, 2019)
The aim of the research was to investigate the rheological behaviour of hydroxyethyl cellulose gels, which are used in the development of the composition and technology of the medicine with anti-inflammatory activity. The objects of research were hydroxyethyl cellulose gels in the concentration of 1.0%; 1.5%; 2.0%; 2.5% and 3.0%. Investigation of the rheological behavior of HEC gels (structural and mechanical properties) was performed using the Rheolab QC rheometer from Anton Paar (Austria) using the C-CC27 / SS Coaxial Cylinder System. The obtained results showed that excipients influence on the rheological behaviour in the following way: propylene glycol and polyethylene oxide 400 reduce rheoparameters, while PEG 40 hydrogenated castor oil increases these parameters. The further study of the rheological properties in comparison with medicines "Troxerutin" and "Thiotriazolinum" showed that the developed gel fully corresponds to technological and consumer requirements.